A percepção de familiares acerca do acolhimento por enfermeiros em unidade de terapia intensiva: revisão integrativa da literatura - SILVA, Josiane Silva da (2019)
The objective of this study was to identify scientific evidence in the literature about the experience of the relatives of patients hospitalized in the Intensive Care Unit (ICU) regarding the reception of the nurse practitioner in this unit. This is an integrative review of literature, which has as a guiding question "What is the perception of the relatives of patients hospitalized in the ICU regarding the nursing professional? Data collection was carried out during the month of May 2018, encompassing research published between 2012 and 2018. The inclusion criteria included primary studies that answered the guiding question of the study in the Portuguese language, excluding editorial, articles of reflection and review, and book chapters. The Virtual Health Library (BVS) through the descriptors / MeSH used the database: host, nurse, nursing unit, intensive care unit, family, nurse-patient relationship, using the boolean "AND" and "OR”. The result of data collection totaled 5 published articles referring to the theme. From the categorization, analysis and interpretation of the articles resulting from the research, three thematic categories emerged: strategies for the reception of relatives hospitalized in uti, communication and emotional preparation and professional qualification. The study revealed that some difficulties in caring for the family are related to the lack of strategies for reception, ineffective communication and fear of emotional involvement, as well as the lack of preparation of the nurse of the intensive care unit. We conclude that with this review, it is reiterated the importance of the valorization of the host to the family as an innovation of the relevant care for the practice, since, the nursing care needs to be seen and understood in a holistic way, perceiving the patient in all the aspects, and this includes your family in the health-disease process.